A Teoria da Justiça entre o Transcendentalismo e o Comparativismo - Cristiano Luiz Girardelli de Barros (2020)
The plural scenario and the crisis of philosophical ethics entailed by the individualistic and technical-scientific rationality of modernity make it very difficult to unify the claims of justice under a single symbolic conception of the just. The revision of the concept of distributive justice, especially from the seventeenth century onwards, concurred to making the theory of justice an ever more challenging task, whose developments also needed to take into account the political right not to live in a state of misery. From the clash between philosophical utilitarianism and the economic sciences came into existence the ideology according to which the automatic functioning of the market would ensure social justice. At its peak, positivist utilitarianism displayed the barrenness of this ideology, the greatest evidence of which would be given by Kenneth Arrow's impossibility theorem. In response to the failure of utilitarianism’s empiricist claims, the second half of the twentieth century witnessed the revival of normative theories, with John Rawls pioneering the rehabilitation of normative political philosophy. In rereading Kantian constructivism, Rawls postulated principles of justice which, in full and perfect operation, could lead modern democratic societies to the just status of well-ordered societies. A friend of Rawls, the Indian economist Amartya Sen, also opposing the sterility of positivist utilitarianism, distanced himself from the Rawlsian approach, labelling it as a transcendental institutionalism whose utopia was alien to the existence of patent injustices that required immediate redress. As the result of years of research and thinking, Sen developed his concept of justice based on the possibility of agreements, partial notwithstanding, in any context, aiming at the removal of blatant injustices, as well as at the expansion of people's capabilities to live the lives they want to live. The present dissertation reconstructs this history, mainly focusing on the dialogue between the theories of John Rawls and Amartya Sen and on the criticism made by both to the utilitarianism that preceded them. Lastly, we assess, in light of Hegel's historicaldialectical approach to philosophy and in accordance with the further developments of Joaquim Carlos Salgado's philosophy of law, how and to what extent Rawls and Sen’s propositions relate to the problem of achieving social justice as one of securing fundamental rights.